Reading Andre Gide’s The Immoralist And Leo Tolstoy’s Anna Karenina Through Feminist Criticism - Diva Wenanda (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2018)
The growing interest in gender issues, relationship, family construct etc can be seen in academic writing or elsewhere. Gender stereotypes obviously have created some impacts on individual behaviors. Such stereotypes consolidate gender behavior practised in society. Mental and physical health are also affected by these stereotypes. Moreover, gender stereotypes affect male and female relationships.            Anna Karenina and The Immoralist were written at different times and places, 1866 and 1902, both of these Novels written by men with their perspective.. The female character in these two novels portray different stereotypes. Female characters lack authenticity if they are not portrayed as the complex and unique individuals. Too often women are merely stereotypes that allow the male protagonist to define his own role and fulfill his own selfhood. In response to this misrepresentation of women in literature, feminist criticism has necessarily often become a negative one, resisting stereotyped images of women.